Multi‐physics modeling of doxorubicine binding to ion‐exchange resin in blood filtration devices. Issue 4 (31st December 2020) - Maani, Nazanin; Balsara, Nitash; Hetts, Steven W.; Rayz, Vitaliy L.
Abstract: A group of drugs used in intra‐arterial chemotherapy (IAC) have intrinsic ionic properties, which can be used for filtering excessive drugs from blood in order to reduce systemic toxicity. The ion‐exchange mechanism is utilized in an endovascular Chemofilter device which can be deployed during the IAC for capturing ionic drugs after they have had their effect on the tumor. In this study, the concentrated solution theory is used to account for the effect of electrochemical forces on the drug transport and adsorption by introducing an effective diffusion coefficient in the advection–diffusion–reaction equation. Consequently, a multi‐physics model coupling hemodynamic and electrochemical forces is developed and applied to simulations of the transport and binding of doxorubicine in the Chemofilter device. A comparison of drug adsorption predicted by the computations to that measured in animal studies demonstrated the benefits of using the concentrated solution theory over the Nernst–Plank relations for modeling drug binding.